FINANCIAL BEHAVIOR PADA MAHASISWA PENERIMA PROGRAM INDONESIA PINTAR (PIP) - bangun Putra prasetya (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Indonesia's national education system has a strategic role in educating the nation's life and advancing science and technology. Based on Law No. 12/2012 concerning Higher Education, the Government of Indonesia is obliged to increase access and learning opportunities at universities and to prepare intelligent and competitive Indonesian people, one of which is the Smart Indonesia Program (PIP) for Lectures. This study aims to analyze the factors that influence the Financial Behavior of PIP recipient students at the Widya Mataram University, Yogyakarta. The population in this study was 251 students while the sample was 99 students. This research method uses descriptive quantitative while the analysis tool uses SEM-PLS. The results showed that of the four exogenous variables, namely Financial Literacy, Financial Self-Efficacy, financial experience, Incomeintention which had a positive effect on Financial Behavior, namely Financial Self-Efficacy and Incomeintention. While the other two variables, namely Financial Literacy and financial experience have no significant effect on Financial Behavior